Conhecimento financeiro de estudantes universitários na vertente do crédito=Financial knowledge of credit among college students - Roquette, I.; Laureano, R. M. S.; Botelho, M. (Tourism and Management Studies, 2014)
Financial markets, increasingly complex and sophisticated, are being developed at an impressive speed. It's necessary to have a good level of financial knowledge to be ready for these constant changes. The consumers with larger financial literacy, that is, those with more financial knowledge, but also greater ability to manage it, are the least vulnerable. In this context, this study evaluates the level of credit knowledge among college students, as well as possible limitations of this knowledge. Through a questionnaire survey to 396 undergraduate students from ISCTE-IUL, the results show that the level of financial knowledge, about credit, is low. Furthermore, the students overestimate their knowledge, that is, the students think they know more than what actually happen. Knowledge is explained by the demographic profile of the student, family background and the student culture and financial inclusion. The knowledge is greater on students attending a course in the business area, which are in the 3rd year and consult some information sources regularly. Students who already have bank accounts also have higher average knowledge.